Manajemen Budaya Pondok Pesantren Roudlotut Tholibin Sirau Kemranjen Banyumas dalam Mengembangkan Kecerdasan Santri - Hidayat, Ayi Najmul; Ratnawulan, Teti; Mujiburrohman, Mujiburrohman; Muhtad, Fauzi Al (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
Islamic boarding schools as the oldest Islamic educational institutions which are considered traditional and which are considered closed to innovation. However, they must be ready to face the challenges of the times and are required to develop the potential of students with the power of knowledge and technology through cultural management at Islamic boarding schools to increase the intelligence of students at Roudlotut Tholibin Sirau Islamic Boarding School, Kemranjen, Banyumas. This study uses a qualitative descriptive method with data collection techniques through documentation, observation, interviews. From this study, the results were obtained that in an effort to improve the three intelligences (intellectual, emotional, and spiritual) which are carried out continuously and consistently through formal education in Islamic boarding schools with good management with a benchmark of success, namely alumni continuing their studies at tertiary institutions both in country or abroad. Keywords: education management, Islamic boarding schools, intelligence